(untitled) (Journal of Academic Research, 2025)
Telemedicine is one of the modern trends in the health field; recently, telemedicine began to have more acceptance and demand due to the huge development in communication technologies, especially after the COVID-19 pandemic. This research aims to evaluate Dietitians’ experiences and patients’ experiences of telenutrition consulting; this research relied on the descriptive approach. The study sample consisted of 61 dietitians and 315 people targeted by telenutritional consulting services. for dietitians who participated in this study, their years of experience varied from one year to more than 10 years, and 83.3% of them had previously provided the remote consultation service. For the remaining 16.4% of them, the reasons for not providing remote consultation were the lack of sufficient training. Their preference for in-person nutritional consulting, The main limitations for remote consultations were lack of easy payment methods at 37.7%, followed by the lack of time at 31.1%, then the lack of the Internet access at 24.6%. In the second part of this study, A total of 315 people responded to a questionnaire in order to survey their opinions and experiences in obtaining nutritional consultations remotely. It was found that 50.2% of them had suffered from health problems related to nutrition, and 21.3% of them had never consulted a dietitian. Our survey indicated that dietitians are increasingly adopting telenutrition consultations. However, patients reported a lack of interest in accessing these consultations. The most frequently reported barriers were the lack of easy online payment methods and the limited communication between dietitians and clients.